Proceedings. 1991 IEEE International Conference on Robotics and Automation
DOI: 10.1109/robot.1991.131765
|View full text |Cite
|
Sign up to set email alerts
|

Parallel algorithms and architecture for computation of manipulator forward dynamics

Abstract: Abstract-In this paper parallel computation of manipulator forward dynamics is investigated. Considering three classes of algorithms for the solution of the problem, that is, the O(n), the O(n2), and the O(n 3) algorithms,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…(2) The (9(n 2) Conjugate Gradient (CG) algorithms [7,8] which iteratively solve equation (1) without explicit computation and inversion of the mass matrix. (3) The (9(n 3) algorithms [7] which solve equation (1) by explicit computation and inversion of the mass matrix, leading to an (9(n 3) computational complexity.…”
Section: F = G(o O (~ O) = G2(o (~)mentioning
confidence: 99%
See 4 more Smart Citations
“…(2) The (9(n 2) Conjugate Gradient (CG) algorithms [7,8] which iteratively solve equation (1) without explicit computation and inversion of the mass matrix. (3) The (9(n 3) algorithms [7] which solve equation (1) by explicit computation and inversion of the mass matrix, leading to an (9(n 3) computational complexity.…”
Section: F = G(o O (~ O) = G2(o (~)mentioning
confidence: 99%
“…In fact, the comparative study in [4] has shown that the C(n 3) Composite Rigid-Body algorithm is the most efficient for n less than 12. It should be pointed out that the efficiency of both the (9(n 3) and the Cg(n 2) algorithms has been recently improved [8,9]. However, despite these improvements, even the fastest serial algorithm is far from providing the efficiency required for real-time or faster-than-real-time simulation.…”
Section: F = G(o O (~ O) = G2(o (~)mentioning
confidence: 99%
See 3 more Smart Citations